(untitled) (Bangladesh Journal of Neurosurgery, 2020)
Background: Cytotoxicity is the toxicity to cell. Any type of brain oedema producing raised intracranial pressure (ICP) which may be a fatal pathological state. Corticosteroid is contraindicated in cytotoxic brain oedema but in vasogenic oedema, it is beneficial. Cytotoxic oedema in its consequences induces vasogenic oedema where the corticosteroid may helpful. Objectives: To determine the effects of corticosteroid on tertiary vasogenic brain oedema from cytotoxic edema. Methods: Total of 328 patients was diagnosed as brain oedema and they had been first time reported & all were admitted in Combined Military Hospital (CMH) Dhaka, between Jan 2017 to Jun 2019. Out of 328 patients, brain oedema due to spontaneous ICHs was 219 (66.77%) and traumatic ICHs were 109(33.33%). Diagnosis was based upon history, clinical examination and non-contrast Computed Tomography (CT) scan of brain. Results: Total 328 admitted patients in CMH Dhaka from Jan 2017-Jun 2019 were included in our study who full-fill the criteria. Males were 231 (70.43%); females were 97(29.57%) and were aged between 1 to 95 year. Intracranial haemorrhage rate among age group less than 55 years old being 76 (34.70%) and 55 years or above 143 (65.30%) of total 219 patients. Traumatic ICHs were 109 and 1 to 44 years age is most vulnerable, 69(63.30%) and 45 years and above 40 (36.70%) patients. Corticosteroid was used after vasogenic brain oedema formation following cytotoxic oedema which was diagnosed mainly radiologically. Cytotoxic oedema induced by 24 hours and vasogenic oedema in two to four days of brain insult. Vasogenic oedema developed in 24 -48 hours, 65 (19.82%) patients and 117 (35.67 %) by 48-72 hours and above 72 hours rest 146 (44.51%) patients after brain insult. After vasogenic oedema formation, out of 164 patients that is 50% patients were treated with corticosteroid and GOS was assessed- GOS 4,5 -103(62.80%), GOS 3-34 (20.73%), GOS 2- 23(14.02%) and GOS 1-4(2.44%) whereas without corticosteroid treatment of rest vasogenic oedema 164 (50%) , GOS was- GOS 4,5 -85(51.83%), GOS 3-43 (26.22%), GOS 2- 27(16.46%) and GOS 1-9(5.49%) at 30 days of incidence. There is more than two times mortality without corticosteroid therapy than with steroid therapy. Conclusion: Cytotoxic brain oedema is contraindicated for steroid but we observed that corticosteroid gives better GOS in vasogenic oedema which develops after cytotoxic brain oedema. Outcome in cytotoxic oedema followed by vasogenic oedema is beneficial for corticosteroid. Bang. J Neurosurgery 2020; 10(1): 45-51